Future flight deck design: developing an innovative touchscreen inceptor combined with the primary flight display - Wang, Yifan; Li, Wen-Chin; Korek, Wojciech Tomasz; Braithwaite, Graham (Elsevier, 2024)
The touchscreen has the potential to optimize the space usage and efficiency of the flight deck. Currently, touchscreens can combine the input and output functions of different systems. However, it does not yet serve as an inceptor to replace the sidestick or control column for aircraft manoeuvres. This study aims to examine the potential of a touchscreen as a flight inceptor compared with a traditional sidestick and gamepad. This research recruited 72 participants who interacted with three inceptors for both an instrument landing with disturbance and without disturbance using the Future System Simulator. The findings demonstrated that pilot performance, system usability and pilots’ situation awareness of touchscreen inceptors were significantly inferior to those of traditional sidesticks and gamepads. Compared to the sidestick and gamepad, the touchscreen provided a poorer situation awareness with the highest supply and demand. In addition, the performance of all inceptors was significantly influenced by disturbance. There is still a long way to go for certification of a touchscreen as an inceptor on the future flight deck. This research showed that even though the touchscreen inceptor scored the lowest on both SUS and SART, the majority of pilots agreed that the touchscreen inceptor provided a better attentional supply in challenging disturbance circumstances, providing proof of concept for its possible inclusion in flight deck design. There is a potential that the emerging touchscreen as an inceptor may develop further along with human-system integration flight deck design.
Keywords: Flight deck design; Human-computer interaction; System usability; Touchscreen inceptor; Visual behaviours